Analisis ekonomi inklusif di Provinsi Kalimantan Barat dan Kalimantan Timur menggunakan data panel - Ahmad Fahri Umardani (Nur Science Institute, 2026)
The purpose of this study is to analyze the effects of the Human Development Index (HDI), Domestic Investment, Open Unemployment Rate, electricity access, and internet access on the Inclusive Economic Development Index (IEDI) in West Kalimantan and East Kalimantan Provinces. The study employs panel data at the district/city level covering the period 2018–2022, sourced from Statistics Indonesia and the National Development Planning Agency (BAPPENAS). Panel data regression is applied as the analytical method. The results indicate that in West Kalimantan, HDI, electricity access, and internet access have positive and significant effects on inclusive economic development. Meanwhile, in East Kalimantan, HDI shows a positive and significant effect, whereas the open unemployment rate significantly affects inclusive economic development. These findings suggest that the determinants of inclusive economic development vary across regions. Therefore, development policies should be region-specific, focusing on improving human capital quality, expanding access to basic infrastructure, and addressing labor market issues in order to promote more inclusive and sustainable economic growth.